13. Arnicetum atlanticae BeIIot 1968 - Ortiz, Santiago; Epelde, Asunción; Rodríguez-Oubiña, Juan (Lazaroa, 2014)
Sobre los aspectos nomenclaturales de este sintaxon, especialmente sobre su autoría, ha habido cierta confusión.